(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the philosophical essence of the principles of social justice and legal equality in the process of forming a democratic rule-of-law state, their historical genesis, and their role in the development of modern society. The study interprets the concepts of justice and equality not only as legal categories, but also as complex philosophical phenomena closely connected with social consciousness, moral values, and political culture. Furthermore, the role of these principles in democratic governance, civil society, and the protection of human rights is examined.